Tensegrity-inspired triboelectric nanogenerator for broadband and impact-resistive vibration sensing. (May 2023) - He, Changliu; Yang, Tingting; Fang, Jiahao; Pu, Xiaobo; Shang, Kedong; Tian, Guo; Lu, Xulei; Wu, Jianbing; Yang, Weiqing; Qian, Linmao
Abstract: Vibration in the environment usually shows uncertainty with random changes in frequency and sudden acceleration impact. However, it is a huge challenge for existing vibration energy harvesters and sensors to work in random and even extreme vibration environments due to their rigid multi-component architecture with mechanical mismatches. Here, we propose a general design of vibration transduction with broadband response and high mechanical robustness that mimics the biological musculoskeletal system. Such design is based on a tensegrity structure, consisting of a rigid frame and soft strings, combined with triboelectric nanogenerator (TENG). The Tensegrity-inspired triboelectric nanogenerator is of broadband (0–200 Hz) frequency response and exhibits excellent impact resistance under high g acceleration impacts (10 5 g level). The device can still work normally after undergoing some structural damage. It has been successfully applied to the aeolian vibration monitoring of transmission lines and shows more reliable performance than commercial sensors when suffering the hail impact. Such tensegrity structure design has great potential in high-performance vibration monitoring in the industrial environment. Graphical Abstract: The tensegrity-inspired triboelectric nanogenerator exhibits reliable vibration sensing and energy harvesting capabilities under complex, varying, and even extreme environments. The device achieves broadband energy harvesting (0–200 Hz). The soft strings in this structure dissipate a large amount of shock energy, allowing the device to withstand acceleration shocks up to 10 5 g levels. The special arrangement of the soft strings allows the device to withstand structural damage. In addition, a wireless aeolian vibration online monitoring system for transmission lines is developed. It's more reliable than some commercial sensors in harsh environments such as hailstorm weather. ga1